2017
DOI: 10.1038/srep41166
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-myoinositol cotransporter-1, SMIT1, mediates the production of reactive oxygen species induced by hyperglycemia in the heart

Abstract: Hyperglycemia (HG) stimulates the production of reactive oxygen species in the heart through activation of NADPH oxidase 2 (NOX2). This production is independent of glucose metabolism but requires sodium/glucose cotransporters (SGLT). Seven SGLT isoforms (SGLT1 to 6 and sodium-myoinositol cotransporter-1, SMIT1) are known, although their expression and function in the heart remain elusive. We investigated these 7 isoforms and found that only SGLT1 and SMIT1 were expressed in mouse, rat and human hearts. In car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 51 publications
2
66
1
Order By: Relevance
“…Balteau et al (28), showed that SGLT1 is linked with NADPH oxidase activation. Later, Van Steenbergen et al (29), found that SGLT1 mediated the production of reactive oxygen species induced by hyperglycemia in the heart. Both NADPH oxidase activation and production of reactive oxygen species enhanced MMP-2 expression and activation.…”
Section: Discussionmentioning
confidence: 99%
“…Balteau et al (28), showed that SGLT1 is linked with NADPH oxidase activation. Later, Van Steenbergen et al (29), found that SGLT1 mediated the production of reactive oxygen species induced by hyperglycemia in the heart. Both NADPH oxidase activation and production of reactive oxygen species enhanced MMP-2 expression and activation.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of response is similar to that seen in the DECLARE‐TIMI 58 trial, which showed the most marked reduction in heart failure events in patients with the lowest ejection fraction before randomization. Taken collectively, these observations suggest that SGLT2 inhibitors exert a direct cardioprotective effect that is proportional to the severity of myocardial stress, even though there is no detectable SGLT2 expression in the heart . Two possible mechanisms have been proposed to account for such a cardioprotective action ( Figure ).…”
Section: Novel Mechanisms By Which Sglt2 Inhibitors May Promote Cardimentioning
confidence: 91%
“…However, excess ROS production leads to pathological states such as heart failure and exacerbation of ischaemic cell death as occurs in ischaemia/reperfusion injury and heart failure. 6 In the heart, SGLT1/SMIT has been linked gp91 phox NADPH oxidase activity 7 , and demonstrated as a cause of myocardial injury. Clinical SGLT2 inhibitors such as Empagliflozin are highly selective towards SGLT2, but others, such as Canagliflozin, have more mixed SGLT2/SGLT1 inhibitory action; SGLT1 inhibition abrogates the excess ROS generation precipitated by pathophysiologically-relevant high glucose in experimental models 7 , and thus raises the hypothesis that SGLT2 inhibitors, either directly through mixed SGLT2/SGLT1 inhibition, or indirectly through improved glycaemic control at the time of the ischaemic insult, may reduce injury through attenuation of oxidant stress in ischaemic tissue.…”
Section: ) the Interaction Between Sglt1/smit And Gp91 Phox Nadph Oxmentioning
confidence: 99%